Real or fake? : far-out fibs, fishy facts, and phony photos to test for the truth - Krieger, Emily; Cocotos, Tom Nick. (Washington, D.C. : National Geographic, 2016)
Offers suspicious stories, fishy facts, and dubious lists, encouraging readers to determine which facts are true and which are false.
Note continued: Town Gets Cut Off -- Real or Fake? Peculiar Place-Names -- Elephants Use Feet to Talk Long-Distance -- Bizarre Bird Baffles Scientists -- Spaghetti Grows on Trees -- Famous Street Artist Arrested -- True Identity Revealed -- One Odd Job -- Real or Fake? Other Odd Jobs -- Spot the Fake! -- Gobi's Giant Worm -- Spacecraft Lands on Comet -- Paint Keeps the Peace -- Countries Battle Over Bird Poop -- Now You Can Visit Seafloor City! -- Identify the Lie! -- Bizarre Burger Beginnings -- Popular Fruit Full of Bugs -- Man Walks o Water -- Spot the Fake! -- Rhino Rambles Across College Campus -- Tornadoes Catch Fire -- Armchair Adventurer Goes Airborne.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Description based on print version record.
Keywords: Curiosities and wonders -- Humor -- Juvenile literature; Curiosities and wonders; Common fallacies; Urban foklore; Truthfulness and falsehood; JUVENILE NONFICTION -- Curiosities & Wonders; Curiosities and wonders; Electronic books- OSLIS; Children's nonfiction; Humor; Juvenile works; Trivia and miscellanea; Trivia and miscellanea; Electronic books